A concepção de deficiência em discussão: ponto de vista de docentes de Terapia Ocupacional - Baleotti, Luciana Ramos [UNESP]; Omote, Sadao [UNESP] (Editora Cubo, 2014)
The way one conceives disabled people seems to influence the actions directed toward them. Occupational therapists constitute a part of health professionals that direct their actions based on a comprehensive view of disability. The aim of this study was to identify and analyze the conception of disability from the standpoint of occupational therapists. Fifteen university teachers of Occupational Therapy undergraduate courses participated in this study: seven from public universities and eight from private institutions, located in mid-sized municipalities in the state of São Paulo. The data were collected by means of a scale denominated “Escala de Avaliação da Concepção de Deficiência” (Rating Scale for Conception of Disability). The results show that the subjects tend to follow interactional, social conceptions of disability. This study yields contributions to understand the conception of disability held by teachers of Occupational Therapy. This conception certainly guides their teaching performance and affects the training of future professionals.

A forma como concebemos as pessoas com deficiência parece influenciar as ações destinadas a elas. Terapeutas ocupacionais representam uma parcela de profissionais da área da saúde que direcionam suas ações pautados em uma visão abrangente do que representa a deficiência. Objetivou-se identificar e analisar a concepção de deficiência na perspectiva de docentes com formação em Terapia Ocupacional. Participaram deste estudo 15 docentes, sendo sete de duas universidades públicas e oito de duas universidades privadas, localizadas em cidades de médio porte do estado de São Paulo. A coleta de dados foi realizada por meio de um instrumento denominado Escala de Avaliação da Concepção de Deficiência. Os resultados apontam que o grupo estudado apresenta maior tendência às concepções interacionista e social de deficiência. O estudo traz contribuições para a compreensão da concepção que os docentes de cursos de Terapia Ocupacional têm acerca da deficiência, o que certamente conduz o fazer pedagógico deles, afetando a formação de futuros profissionais.
The conception of disability under discussion: the point of view of Occupational Therapy professors
Keywords: Concepção de deficiência; Terapia Ocupacional